Hidroformilação do isopreno e de olefinas de origem natural catalisada por complexos de ródio: efeito da conjugação na reatividade do substrato - Humberto James do Val Barros (2007)
This abstract presents the main advances obtained in this dissertation work, concerning the preparation of aldehydes through olefin hydroformylation reaction, using isoprene, monoterpenes, and propenylaromatic substrates. Rhodium catalyzed hydroformylation of isoprene was studied in the presence of various mono- and diphosphines. Using a large excess of the ligand, the reaction can be performed under mild conditions (80-100oC, 40-80 atm) and yields three unsaturated aldehydes, formed in a 95% combined selectivity. The study of the effects of the reaction variables revealed remarkable trends, opposite to those usually observed with simple alkenes. The increase in the concentration of the phosphorus ligand and/or ligand basicity strongly accelerates the reaction. Moreover, the reaction shows unusual kinetics, being first order in both hydrogen and CO pressure under "common" hydroformylation conditions. The obtained data confirm that a 3- 1-rearrangement, which converts a CO insertion resistant 3-allyl rhodium intermediate into the much more reactive 1-complex, is the most critical step of this reaction. The hydroformylation reactions, which the model molecule isoprene undergoes, were attempted with the natural monoterpenes myrcene and limonene. These cheap substrates are widely found in Brazil and have olefinic bonds. The myrcene molecule has two conjugated double bonds, while limonene does not. In fact, limonene showed common behaviour for monoenes, since its activity is low with large excess of the phosphorus ligand. The reactions with myrcene were similar to those of isoprene, inasmuch the increase in the P/Rh ratio up to a limit value significantly accelerates them. In this way, it was possible to develop an efficient process, under mild conditions, to hydroformylate open chain conjugated dienes with rhodium catalyst and the low cost, readily accessible triphenylphosphine ligand. It was also studied the hydroformylation of propenylaromatic compounds, using quiral ligands, to develop an asymmetric induction process. The aldehydes were obtained with high chemo- and regiosselectivity, but with low enantiomeric excess. The rhodium catalyzed hydroformylation of myrcene, limonene, and camphene was achieved in a toluene/water biphasic system employing tris(3-sulfonatophenyl)phosphine trisodium salt (tppts) and 3-sulfonatophenylphosphine monosodium salt (tppms) as ancillary ligands, with various concentrations of the cationic surfactant cetyltrimethylammonium chloride (CTAC). In some instances, the observed conversion rates were superior to the similar homogeneous systems. The promotion effect of CTAC and its optimal concentration depend on the conformational characteristics of the substrate. For myrcene, a pronounced promotion effect was observed for CTAC concentrations around 2.5 x 10-2 mol.L-1, whereas for camphene there was an inhibition effect even at concentrations as low as 2.5 x 10-3 mol.L-1. Based on the obtained results, it was possible to develop an efficient and selective process for natural olefin hydroformylation to produce interesting intermediates for use in fine chemistry.